2022
DOI: 10.1016/j.ekir.2021.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Germline Mutations for Kidney Volume in ADPKD

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…31 PKD1 splicing and frameshift mutations are associated with TKV ≥1000 mL or Mayo subclass 1C-1E. 32 With more than 2000 mutations identified to date, the genetics of ADPKD is becoming more complex (ADPKD Mutation Database: [http://pkdb.…”
Section: Computed Tomography/magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…31 PKD1 splicing and frameshift mutations are associated with TKV ≥1000 mL or Mayo subclass 1C-1E. 32 With more than 2000 mutations identified to date, the genetics of ADPKD is becoming more complex (ADPKD Mutation Database: [http://pkdb.…”
Section: Computed Tomography/magnetic Resonance Imagingmentioning
confidence: 99%
“…Truncating mutations are associated with an earlier age of ESKD onset than non‐truncating mutations 31 . PKD1 splicing and frameshift mutations are associated with TKV ≥1000 mL or Mayo subclass 1C–1E 32 . With more than 2000 mutations identified to date, the genetics of ADPKD is becoming more complex (ADPKD Mutation Database: [http://pkdb.mayo.edu]).…”
Section: Diagnosismentioning
confidence: 99%
“…Fröhlich et al identified the following challenges in data science (artificial intelligence [AI]/machine learning) for personalized medicine (1): insufficient prediction performance for clinical practice (2), difficulties in interpretation, and (3) insufficient validation for clinical practice (105). Indeed, unlike in genetic diseases (106) where personalized medicine can be applied according only to genetic mutations (107)(108)(109)(110), most patients with CKD are affected by multiple risk factors for disease progression (111,112). In patients with CKD, the risk factors and pathophysiological conditions generally differ regarding patient attributes (113).…”
Section: Attribute-based Medicine For Personalized Medicinementioning
confidence: 99%